2010
DOI: 10.1016/j.cortex.2009.04.011
|View full text |Cite
|
Sign up to set email alerts
|

There are age-related changes in neural connectivity during the encoding of positive, but not negative, information

Abstract: Introduction-Older adults often show sustained attention toward positive information and an improved memory for positive events. Little is known about the neural changes that may underlie these effects, although recent research has suggested that older adults may show differential recruitment of prefrontal regions during the successful encoding of emotional information. In the present study, effective connectivity analyses examined the network of regions that college-age and older adults recruited during the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 47 publications
6
76
1
2
Order By: Relevance
“…This result was interpreted as evidence that older adults compensate for hippocampal deficits by relying more on the parahippocampal cortex. Similar results have been reported in studies that measured brain activity during successful encoding of words 91 , scenes 92 or objects 93 by comparing encoding activity for subsequently remembered versus forgotten stimuli. In these studies, functional connectivity during successful encoding between MTL regions and posterior regions, such as occipital cortex, was weaker in old adults, but connections between the MTL and the PFC were stronger in the older adults compared to a younger group.…”
Section: Box 1 Measuring Activity In Brain Networksupporting
confidence: 83%
“…This result was interpreted as evidence that older adults compensate for hippocampal deficits by relying more on the parahippocampal cortex. Similar results have been reported in studies that measured brain activity during successful encoding of words 91 , scenes 92 or objects 93 by comparing encoding activity for subsequently remembered versus forgotten stimuli. In these studies, functional connectivity during successful encoding between MTL regions and posterior regions, such as occipital cortex, was weaker in old adults, but connections between the MTL and the PFC were stronger in the older adults compared to a younger group.…”
Section: Box 1 Measuring Activity In Brain Networksupporting
confidence: 83%
“…This is the first study to our knowledge to demonstrate reduced cortical reactivity to emotional arousal in healthy aging. Aging has been associated with the experience of fewer negative emotions (Gruenewald et al, 2008;Mroczek and Kolarz, 1998), as well as reduced neural processing of negative compared with positive emotional stimuli (Addis et al, 2010;Leclerc and Kensinger, 2008;Mather et al, 2004). Considering that negative emotional stimuli tend to be rated as more arousing than positive stimuli (Lang et al, 2008), and tend also to result in greater BOLD signal increases in emotional and visual brain regions than neutral or positive images (e.g., Lane et al, 1997;Mourão-Miranda et al, 2003), it is possible, based on our results, that an under-responsiveness in older adults to the effects of arousal may partly mediate the attenuation in their response to negative emotional stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Age-related positivity effects may be informed by a bias in the processing of emotional stimuli that emerges as previously unused neural networks are engaged due to age-related changes in functional organization of the brain. For instance, Addis et al (2010) have shown that, unlike in younger controls, successful encoding of positive information in older adults is accompanied by strong neural activity between typically emotionally-involved areas, such as the ventromedial pre-frontal cortex and the amygdala, and the hippocampus. These results suggest that emotional processing in older adults may be altered as a consequence of play an important role especially through its general support of neural compensation.…”
Section: Cognitive Reserve and Positivity Effect 15mentioning
confidence: 99%
“…Moreover, older adults are thought to receive a memory boost for positively valenced information. However, this latter finding has been disputed, with some reports confirming it (Addis, Leclerc, Muscatell & Kensinger, 2010;Charles, Mather & Carstensen, 2003;Grady, Hongwanishkul, Keightley, Lee & Hasher, 2007;Kensinger, Garoff-Eaton & Schacter, 2007), while others have not found supporting evidence, or have qualified it (Emery & Hess, 2008;Kapucu, Rotello, Ready & Seidl, 2008;Kensinger, 2008).…”
Section: Introductionmentioning
confidence: 99%